Wybrane problemy funkcjonowania Polskiej Komisji Akredytacyjnej na podstawie przepisów ustawy Prawo o szkolnictwie wyższym i nauce – stan obecny i perspektywy zmian - Wundziński, Karol (Studia Prawa Publicznego, 2025)
The article concerns the legal basis for the functioning of the Polish Accreditation Commission (PKA) and the role it plays in ensuring the quality of education on degree courses run in Polish higher education institutions. The PKA, as a state institution, was established to verify the fulﬁlment of international educational quality standards for ﬁrst- and second-cycle studies and to support higher education institutions in improving the educational process by fostering a culture of quality. Its establishment is directly related to Poland’s accession to the European Higher Education Area and the implementation of the Bologna Process. The author analyses the evolution of legal regulations concerning the PKA, which leads to the conclusion that the current legal status does not precisely deﬁne the legal status and forms of the PKA’s activity, which raises numerous doubts concerning the nature of the decisions issued by it and the accreditation procedures adopted. He further diagnoses and discusses in detail the main problems, which include the nature of its programme evaluation procedure, the legal qualiﬁcation of a PKA presidium resolution, and the possibility of judicial review of decisions on programme evaluation. In the conclusions, the author points to the need to ensure judicial control of the PKA Presidium’s resolutions. He also draws attention to the need to clarify its role in the higher education system as a speciﬁc administrative entity. The author emphasises that the lack of clarity in the legal regulation negatively affects the legal situation of universities and their procedural rights. Finally, possible directions of changes in the legislation to ensure better transparency and control of PKA’s activities are presented.